PELATIHAN DIGITALISASI DATA ALUMNI GUNA MENDUKUNG EKOSISTEM SEKOLAH SWASTA YANG BERKELANJUTAN - Kusumawati, Kiki; Hendradi, Prionggo; Dewi, Yusriani Sapta; Nurhayati, Nurhayati; Raihan, Achmad (Jurnal AbdiMas Nusa Mandiri, 2026)
At Alumni data management at SMK Grafika Jakarta Selatan has been carried out conventionally through recording in books and simple worksheets by the school and alumni association administrators. The conventional or manual procedures have caused various obstacles, including data inaccuracy, slow Digital transformation in educational data management is a strategic priority for vocational schools, particularly in supporting tracer studies and data-driven quality enhancement. This community engagement project aimed to design and implement a web-based alumni management information system at SMK Grafika Jakarta Selatan through the Graftur Connect application. The institution previously relied on manual alumni data management, resulting in inefficiencies, data inaccuracies, and limited analytical capability. The project was conducted in four stages: needs assessment, system development, user training, and evaluation based on Kirkpatrick’s Level 1 (reaction) model. The system was developed using the Laravel framework with a structured database to manage alumni profiles, employment history, tracer study data, communication features, and digital alumni ID services. The training session involved 40 participants, including school administrators and alumni representatives. Findings indicate a positive user response, with participants acknowledging the system’s usability, relevance, and effectiveness in improving data management processes. The digital platform enhanced data accuracy, accessibility, and institutional engagement with graduates. Overall, the initiative contributes to establishing a structured, adaptive, and data-driven alumni management framework within the vocational education sector.